Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1785/0120000242
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Scaling Laws for Truck Bomb Explosions Based on Seismic and Acoustic Data

Abstract: We analyze seismic and acoustic data from a series of controlled truck bomb explosions to develop scaling laws and functional relations between charge size and various waveform properties. The explosions had yields of 3-12 ‫ן‬ 10 3 kg trinitrotoluene (TNT), and the receivers were placed at distances of 1-16 km, so the data mimic the data previously recorded from actual terrorist truck bombings. We examine four airblast properties (peak overpressure, impulse per unit area, pulse duration, and average shock velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 20 publications
3
39
0
Order By: Relevance
“…Note that these first-arriving P-wave velocity records are very simple and remarkably similar across the recording network in both directions. The amplitudes vary slightly less quickly than 1=r 2 as expected from previously reported studies (e.g., Flynn and Stump, 1988;Reamer and Stump, 1992;Koper et al, 2002), as the scaled amplitudes in Figure 5 increase with range.…”
Section: Seismic Data and Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Note that these first-arriving P-wave velocity records are very simple and remarkably similar across the recording network in both directions. The amplitudes vary slightly less quickly than 1=r 2 as expected from previously reported studies (e.g., Flynn and Stump, 1988;Reamer and Stump, 1992;Koper et al, 2002), as the scaled amplitudes in Figure 5 increase with range.…”
Section: Seismic Data and Methodssupporting
confidence: 86%
“…This measurement takes the PPV in the seismogram in the time window between the first P wave and the air-blast arrival (∼330 m=s) and thus impacted by the waveform variability seen in Figure 3. We found that this variability made the low-frequency spectral measurement of Koper et al (2002) highly path dependent (up to a factor of 10) and an undesirable candidate for a transportable estimator of source properties. suggests that the amplitude of the first P-wave arrival is less affected by the path-dependent propagation as shown by Figure 3.…”
Section: Seismic Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Birds have sometimes been observed to respond to these precursor seismic waves a few seconds before the arrival of a loud sonic boom [21]. Precursor seismic waves have also been observed in short range measurements using blank pistol shots as the acoustic source [22], and in long range measurements using large explosive charges [15,16,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Equation (1) has the nice property of producing an impulse of unit amplitude. Other blast wave characterizations will be used along with scaling curves for both period and amplitude (e.g., Koper et al, 2002) as work progresses. Equation (1) contains three parameters that are unknown in practice and must be estimated through some means ðs 0 ; f c ; AÞ where we note that A is not in Eq.…”
Section: N-wave Detectormentioning
confidence: 99%